Spatial transcriptomics reveals strong association between SFRP4 and extracellular matrix remodeling in prostate cancer - Maria K. Andersen; Sebastian Krossa; Elise Midtbust; Christine A. Pedersen; Maximilian Wess; Therese S. Høiem; Trond Viset; Øystein Størkersen; Ingunn Nervik; Elise Sandsmark; Helena Bertilsson; Guro F. Giskeødegård; et al. (Communications Biology)
Abstract Prostate tumor heterogeneity is a major obstacle when studying the biological mechanisms of molecular markers. Increased gene expression levels of secreted frizzled-related protein 4 (SFRP4) is a biomarker in aggressive prostate cancer. To understand how SFRP4 relates to prostate cancer we performed comprehensive spatial and multiomics analysis of the same prostate cancer tissue samples. The experimental workflow included spatial transcriptomics, bulk transcriptomics, proteomics, DNA methylomics and tissue staining. SFRP4 mRNA was predominantly located in cancer stroma, produced by fibroblasts and smooth muscle cells, and co-expressed with extracellular matrix components. We also confirmed that higher SFRP4 gene expression is associated with cancer aggressiveness. Gene expression of SFRP4 was affected by gene promotor methylation. Surprisingly, the high mRNA levels did not reflect SFRP4 protein levels, which was much lower. This study contributes previously unknown insights of SFRP4 mRNA in the prostate tumor environment that potentially can improve diagnosis and treatment.